Hábitat anfibio adaptativo para ecosistemas inundables (2021)
Under the guideline of proper management of the low-tide area and the seafront, the adequate promotion and spatial organization of housing is proposed that allows the inclusion of facilities and the establishment of new opportunities and activities for the population, better housing conditions, employment opportunities, development. economic and industrial, quality of study and training for the population and satisfy the basic human conditions that are necessary and in many cases precarious for the vast majority of the inhabitants of the region.